INKUBATOR BISNIS SEBAGAI PENGUATAN FAKTOR PENDUKUNG MINAT WIRAUSAHA MAHASISWA - Mulyanto, Dody; Budi, Agustyarum Pradiska (STIE Atma Bhakti, 2024)
The level of interest in entrepreneurship among students remains relatively low, with the majority of students opting to pursue employment post-graduation. Efforts from universities are necessary to boost entrepreneurial interest, thereby creating job opportunities and reducing unemployment rates. This research aims to examine how strengthening business incubators influences the impact of self-efficacy, digital literacy, and entrepreneurial literacy on students' interest in entrepreneurship. The study adopts a quantitative approach, employing data collection methods such as questionnaires and interviews. The study population consists of vocational students attending vocational colleges in Surakarta City. Data analysis utilizes Moderating Regression Analysis (MRA). The findings suggest that business incubators play a significant role in moderating the influence of self-efficacy, digital literacy, and entrepreneurial literacy on students' interest in entrepreneurship. Recommendations include vocational colleges continuing to develop and enhance the effectiveness of business incubators to stimulate students' interest in entrepreneurship. Future research should consider broader subjects beyond just vocational college students.